Unveiling the Public Sector Hold: Egyptian Women and Work-Life Balance - Gadelhak, Safa (AUC Knowledge Fountain, 2025)
Educated women in Egypt view the public sector as their preferred employer, irrespective of their educational level or recent efforts towards women empowerment and the rise of digitization. This study attempts to understand the perceptions of working women, through analyzing their reasons whether prominent or underlying to make this career choice. To better understand this behavior, twenty semi-structured interviews and two focus group discussions were conducted with a total of thirty women from both public and private sectors. The findings revealed that women gravitate towards the public sector mainly because of five reasons: (a) convenient working conditions, (b) feeling stuck, (c) leading parallel jobs, (d) civic responsibility and (e) societal expectations and cultural norms. The study concludes with recommendations for policy makers, to equip women from a youthful age with relevant education and qualifications that would equip them for the modern work environment and making the workplace more accessible and accommodating for women. It is worth mentioning though, that employment has ceased in the public sector in Egypt and has become an artifact of the past.